Prevalence and Predictors of Overweight and Obesity Among a Multiethnic Population of Pediatric Acute Lymphoblastic Leukemia Survivors: A Cross-Sectional Assessment. Issue 6 (August 2016) - Brown, Austin L.; Lupo, Philip J.; Danysh, Heather E.; Okcu, Mehmet F.; Scheurer, Michael E.; Kamdar, Kala Y.
Abstract : As previous studies of obesity in survivors of pediatric acute lymphoblastic leukemia (ALL) have primarily been conducted among non-Hispanic white survivors or children treated on older protocols, our objective was to describe the prevalence and correlates of overweight status among an ethnically diverse population of pediatric ALL survivors, largely treated with more contemporary therapies. We evaluated the overweight/obesity status of pediatric ALL survivors (n=406) followed in the Texas Children's Cancer Center between 2004 and 2014. Survivors were classified as underweight, normal weight, overweight, or obese on the basis of their body mass index at their most current follow-up visit. Our results showed that Hispanic ethnicity (39% of the subjects) was associated with being overweight (adjusted odds ratio=1.88; 95% confidence interval, 1.13-3.14) or obese (adjusted odds ratio=2.84; 95% confidence interval, 1.59-5.06) at follow-up, even after adjusting for cranial radiotherapy (CRT) exposure. Body mass index z -score at diagnosis was also associated with overweight/obesity at follow-up. In addition, there was a statistically significant interaction between younger age at diagnosis and CRT, indicating that younger age at diagnosis was associated with obesity among patients who received CRT. These findings may help identify pediatric ALL patients that are at increased risk of being overweight or obese after treatment.